Fabric, thread and needles: a narrative for Zuzu Angel - Simili, Ivana Guilherme [UNESP]; Morgado, Debora Pinguello (Univ Estado Santa Catarina-udesc, 2015)
In the 1960s, while the Brazilian fashion followed the European standards Zuzu Angel proclaimed, between chintz and laces, I am the brazilian fashion. The text content consists on identifying Zuzu Angel aesthetic production contributions in the creation of brazilian fashion representations and also about the appropriation of not so noble fabrics, of cloths used for home decoration and of thread and needle handicrafts in the construction of clothes made for the elite, which constitutes an example of reuse in fashion. The methodology uses the clothes as texts-documents to the narrative of its trajectory. Linked to the history of fashion, women and the contents of the movie Zuzu Angel, we unravel aspects of female culture in its relationship with the domesticity, public and political in the troubled 1960s and 1970s with fabrics, thread and needle, Zuzu wrote a history in fashion and in the fight against the civil military dictatorship.
Keywords: ANGEL, Zuzu, 1976; Clothes; Fashion - Brazil; Politics